Effects of Corporate Governance on the Performance of State-Owned Enterprises - Heo, Kyoungsun (World Bank, Washington, DC, 2018)
State-owned enterprises play an important role in economic growth and the delivery of critical public services such as health, education, water, and energy. The underperformance of state-owned enterprises can lead to significant challenges in overall national growth and competitiveness and pose a fiscal risk to the government. Consequently, improving the performance of state-owned enterprises remains an important issue for policy makers and development practitioners. More recently, efforts to strengthen corporate governance have been gaining international momentum as a means to improve the performance of state-owned enterprises. This study aims to examine the relationship between corporate governance and the performance of state-owned enterprises. Using data from 320 state-owned enterprises in the Republic of Korea, the study examines the effects of corporate governance on various measures of state-owned enterprise performance, including performance evaluation results, customer satisfaction, and financial performance. The empirical results indicate that board size, corporatization, and transparency and disclosure are positively related to the performance of state-owned enterprises, suggesting that they have an impact on the efficiency of state-owned enterprises. Independence of the board of directors and separation between the positions of board chair and chief executive officer have an insignificant or negative impact on specific measures of performance. These results suggest that a larger board, corporatization of state-owned enterprises, and more transparent disclosure practices can be beneficial for the performance of state-owned enterprises.